Powder and method for producing powder

By setting the molar ratio of Al2O3·SiO2 to 2.1 or above, and using heat treatment and acid treatment technology, powders with novel porous structure are prepared, which solves the problem of single powder structure in the prior art and achieves efficient adsorption and catalytic performance.

JP7656761B1Active Publication Date: 2025-04-03JFE MINERAL CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024138992
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-08-20
Publication Date
2025-04-03
Estimated Expiration
2044-08-20

AI Technical Summary

Technical Problem

The prior art is difficult to provide a powder with novel porous structure and a method for producing the powder.

Method used

By setting the molar ratio of Al2O3·SiO2 to 2.1 or above, a powder with complex pore structures having multiple pore sizes is formed using nanotube-shaped particles, and the physical properties of the powder are adjusted by heat treatment and acid treatment.

Benefits of technology

The novel porous structure of the powder is achieved, which improves the specific surface area and total pore volume of the powder, and enhances its adsorption and catalytic properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007656761000001_ABST
    Figure 0007656761000001_ABST
Patent Text Reader

Abstract

To provide a powder having a novel porous structure that has never been seen before. SOLUTION: The powder contains aluminosilicate particles having a molar ratio of SiO2 content to Al2O3 content of 2.1 or more, the aluminosilicate particles including nanotube particles.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a powder. More specifically, the present invention relates to a powder comprising aluminosilicate particles. The present invention also relates to a method for producing the powder. [Background technology]

[0002] Patent Document 1 discloses a powder containing granules formed by aggregation of halloysite containing halloysite nanotubes. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2018 / 079556 Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present invention is to provide a powder having a novel porous structure that has not been seen before, and also to provide a method for producing the powder. [Means for solving the problem]

[0005] As a result of extensive research into achieving the above-mentioned object, the present inventors discovered that by setting the molar ratio of the SiO2 content to the Al2O3 content within a specific range, a powder having a novel porous structure can be obtained, and thus completed the present invention.

[0006] That is, the present invention provides the following [1] to

[15] . [1] A powder containing aluminosilicate particles having a molar ratio of SiO2 content to Al2O3 content of 2.1 or more, The powder, wherein the aluminosilicate particles comprise nanotube particles. [2] The powder according to [1], wherein the aluminosilicate particles have pores having a pore size of more than 8 nm and not more than 200 nm. [3] The powder according to [1] or [2], wherein the aluminosilicate particles have first pores derived from the nanotube particles and second pores different from the first pores. [4] The powder according to any one of [1] to [3], wherein the aluminosilicate particles have pores having a pore size of 8 nm or less. [5] The powder according to any one of [1] to [4], wherein the aluminosilicate particles have pores having a pore size of 8 nm or less and pores having a pore size of more than 8 nm and not more than 200 nm. [6] The powder according to any one of [1] to [5], wherein the aluminosilicate particles have first pores derived from the nanotube particles and having a pore size of more than 8 nm and not more than 200 nm, second pores different from the first pores and having a pore size of more than 8 nm and not more than 200 nm, and pores having a pore size of 8 nm or less. [7] BET specific surface area is 50m 2 / g or more. [8] The total pore volume is 0.40 cm 3 / g or more. [9] The volume of the micropore is 0.01 cm 3 / g or more.

[10] The amount of water vapor adsorbed is 120 cm at a relative pressure of 0.9. 3 / g or more.

[11] The amount of toluene vapor adsorbed is 40 cm at a relative pressure of 0.9. 3 / g or more.

[12] The powder according to any one of [1] to

[11] , in which the amount of desorbed NH3 at 400°C or higher measured by a temperature programmed desorption method is 4.0 μmol / g or more.

[13] The powder according to any one of [1] to

[12] , having an adsorption amount of methylene blue of 40 mg / g or more.

[14] The powder according to any one of [1] to

[13] , having an average particle size of 0.5 to 200 μm.

[15] A powder containing aluminosilicate particles is calcined at 600 to 900 ° C to obtain a calcined powder; A method for producing a powder, comprising subjecting the calcined powder to an acid treatment, the aluminosilicate particles include nanotube particles; The aluminosilicate particles have a molar ratio of SiO2 content to Al2O3 content of less than 2.1. Effect of the Invention

[0007] According to the present invention, it is possible to provide a powder having a novel porous structure, and also to provide a method for producing the powder. [Brief description of the drawings]

[0008] [Figure 1] This is a TEM image of metahalloysite nanotube particles. [Diagram 2] This is a TEM image of acid-treated metahalloysite nanotube particles. [Diagram 3] 1 is an XRD chart of sintered powder and unsintered powder. [Figure 4] 1 is a graph showing the relationship between the acid treatment temperature and SiO2 / Al2O3 after the acid treatment. [Diagram 5] This shows the relationship between the SiO2 / Al2O3 and the BET specific surface area of ​​the powder produced by adjusting the acid treatment conditions for the sintered powder, which was fired at 900°C in the firing process. [Figure 6] This shows the results of the BET specific surface area when adjusting SiO2 / Al2O3 and changing the firing temperature in the post-firing process. [Figure 7] This shows the total pore volume when adjusting SiO2 / Al2O3 and changing the firing temperature in the post-firing process. [Figure 8] This shows the results of pore size distribution analysis by the BJH method for powder that was post-sintered at 500°C. [Figure 9] This shows the results of pore size distribution analysis by the BJH method for powder that was post-sintered at 900°C. [Figure 10] This is an SEM image of the calcined powder (SiO2 / Al2O3=2.0) before acid treatment. [Figure 11] This is an SEM image of the calcined powder (SiO2 / Al2O3=2.0) before acid treatment. [Figure 12] This is an SEM image of the powder (SiO2 / Al2O3=13.7) that was post-sintered at 900℃. [Figure 13] This is an SEM image of the powder (SiO2 / Al2O3=13.7) that was post-sintered at 900℃. [Figure 14] This shows the results of pore size distribution analysis by GCMC method for powder that was post-sintered at 500°C. [Figure 15] This shows the results of pore size distribution analysis by GCMC method for powder that was post-sintered at 900°C. [Figure 16] Water adsorption isotherm for powders post-calcined at 500°C. [Figure 17] 1 shows the water adsorption isotherm for the powder post-calcined at 900° C. [Figure 18] This is the adsorption isotherm of toluene for the powder that was post-calcined at 500°C. [Figure 19] This is the adsorption isotherm of toluene for the powder that was post-calcined at 900°C. [Figure 20] This shows the results of NH3-TPD measurement of powder that was post-calcined at 500°C. [Figure 21] This shows the results of NH3-TPD measurement of powder that was post-calcined at 900°C. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, a numerical range expressed using "~" means a range that includes the numerical values ​​before and after "~" as the lower and upper limits.

[0010] [Powder] The powder of the present invention contains aluminosilicate particles having a molar ratio of SiO2 content to Al2O3 content of 2.1 or more. The aluminosilicate particles include nanotube particles.

[0011] The content of the aluminosilicate particles is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more, based on the total mass of the powder of the present invention. The upper limit of the content of the aluminosilicate particles in the powder of the present invention is not particularly limited, and may be 100% by mass based on the total mass of the powder. That is, the powder of the present invention may be composed of aluminosilicate particles.

[0012] In the aluminosilicate particles contained in the powder of the present invention, the molar ratio of the SiO2 content to the Al2O3 content (hereinafter also simply referred to as "SiO2 / Al2O3") is 2.1 or more. The SiO2 / Al2O3 in the aluminosilicate particles can be appropriately adjusted depending on the application of the powder, but for example, in terms of increasing the BET specific surface area described below, it is preferably 2.5 or more, more preferably 3.0 or more, and even more preferably 5.0 or more. The upper limit of SiO2 / Al2O3 is not particularly limited, but examples include 10,000 or less and 1,000 or less, preferably 500 or less, more preferably 300 or less, and even more preferably 200 or less. SiO2 / Al2O3 is determined by X-ray fluorescence (XRF) analysis. Specifically, analysis is performed by XRF under the following conditions, and the SiO2 / Al2O3 ratio is calculated from the obtained SiO2 and Al2O3 contents. Equipment used: ZSX Primus IV (Rigaku) ·Pretreatment method: Glass bead method using Li2B4O7 flux Quantitative method: Refractory Technology Association's standard sample for X-ray fluorescence analysis (clay brick standard sample series) and calibration curve method using other reagents

[0013] The aluminosilicate particles contained in the powder of the present invention include nanotube particles. The aluminosilicate particles may be composed of a single nanotube-shaped particle. Alternatively, the aluminosilicate particles may be secondary particles containing nanotube-shaped particles as primary particles. In other words, the aluminosilicate particles may be aluminosilicate granules containing nanotube-shaped particles. In addition, when the aluminosilicate particles are aluminosilicate granules, there is no particular limitation as long as the primary particles include nanotube particles, and other particles than the nanotube particles may be included as primary particles. The content of the nanotube particles in the aluminosilicate granules is preferably 50 mass% or more, more preferably 70 mass% or more, and even more preferably 90 mass% or more, based on the total mass of the aluminosilicate granules. The upper limit of the content of the nanotube particles is not particularly limited, and may be 100 mass% based on the total mass of the aluminosilicate granules. In other words, the aluminosilicate granules may be granules formed by the aggregation of nanotube particles.

[0014] The aluminosilicate particles contained in the powder of the present invention preferably have pores derived from the nanotube particles. The nanotube particles are preferably particles derived from halloysite nanotubes, which will be described later. Halloysite is a clay mineral represented by Al2Si2O5(OH)4·2H2O or Al2Si2O5(OH)4. That is, the SiO2 / Al2O3 (molar ratio) in halloysite is generally 2.0. Halloysite generally exhibits a variety of shapes, such as tubular (hollow tubular), spherical, angular nodules, plates, and sheets. The inner diameter (diameter of the tube hole) of the halloysite nanotube particle, which is a tubular (hollow tubular) halloysite, is, for example, about 10 to 20 nm. It is generally said that the outer surface of the halloysite nanotube particle is mainly made of silicate (SiO2) and the inner surface is mainly made of alumina (Al2O3).

[0015] In addition, particles derived from halloysite nanotubes are a concept that includes halloysite nanotube particles and particles obtained by subjecting halloysite nanotube particles to the treatment described below (hereinafter also referred to as "modified halloysite nanotube particles"), with modified halloysite nanotube particles being preferred. Examples of modified halloysite nanotube particles include metahalloysite nanotube particles obtained by calcining halloysite, and acid-treated metahalloysite nanotube particles obtained by subjecting metahalloysite nanotube particles to an acid treatment, with the acid-treated metahalloysite nanotube particles being preferred. The aluminosilicate particles contained in the powder of the present invention may include halloysite nanotube particles and modified halloysite nanotube particles. Also, the aluminosilicate particles contained in the powder of the present invention may include two or more types of modified halloysite nanotube particles. The method for obtaining the modified halloysite nanotube particles and the physical properties of the modified halloysite nanotube particles will be described in detail later.

[0016] The preferred properties of the powder of the present invention will now be described, followed by a description of the method for obtaining the powder of the present invention.

[0017] <Pore> The aluminosilicate particles contained in the powder of the present invention preferably have pores. The pores are preferably, for example, pores with a pore diameter of more than 8 nm and not more than 200 nm. The presence or absence of pores can be confirmed by measuring an adsorption isotherm. Specifically, a nitrogen adsorption isotherm is obtained, and the nitrogen adsorption isotherm is analyzed by the BJH (Barrett-Joyner-Halenda) method, and a plot (Log differential pore volume distribution) is created with pore diameter on the horizontal axis and differential pore volume on the vertical axis, thereby confirming the presence or absence of pores in the above pore diameter range. The measurement conditions for obtaining the nitrogen adsorption isotherm will be described in detail in the Examples section below. The same applies to the other measurement conditions below.

[0018] In addition, the aluminosilicate particles contained in the powder of the present invention preferably have first pores derived from nanotube particles and second pores different from the first pores. The first pores preferably correspond to the tube pores of the nanotube particles. The second pores preferably correspond to the interparticle voids of the nanotube particles contained in the aluminosilicate particles (preferably aluminosilicate granules). The pore diameters of the first pore and the second pore are preferably both in the range of more than 8 nm and not more than 200 nm, and are preferably both in the range of 10 to 100 nm. The pore diameter of the first pore is preferably in the range of 10 to 20 nm. It is also preferable that the Log differential pore volume distribution analyzed by the BJH method shows two or more pore diameter peaks in the above range. In aluminosilicate granules, a pore size peak corresponding to the interparticle voids (secondary pores) of the nanotube particles is often observed. The presence or absence of pores having a pore size greater than 8 nm and equal to or less than 200 nm, and the presence or absence of the first pores and the second pores can also be confirmed by observing aluminosilicate particles (preferably aluminosilicate granules) with a scanning electron microscope (SEM). When the surface of the aluminosilicate granule is observed by SEM, the presence of the first pores derived from the tube structure of the nanotube particles can be confirmed, and when the cross section of the aluminosilicate granule is observed by SEM, the presence of the second pores can be confirmed. For example, the cross section of the aluminosilicate granule can be observed by cutting the aluminosilicate granule with a focused ion beam (FIB) to obtain a sample and then observing the sample.

[0019] The aluminosilicate particles contained in the powder of the present invention preferably have a third pore having a pore size of 8 nm or less. The third pore having a pore size of 8 nm or less may be present together with the pores having a pore size of more than 8 nm and less than 200 nm. That is, the aluminosilicate particles contained in the powder of the present invention may have a third pore having a pore size of 8 nm or less and a pore having a pore size of more than 8 nm and less than 200 nm. The aluminosilicate particles contained in the powder of the present invention may also have the first pore having a pore size of more than 8 nm and less than 200 nm, the second pore having a pore size of more than 8 nm and less than 200 nm, and the third pore having a pore size of 8 nm or less. The aluminosilicate particles contained in the powder of the present invention may not have the second pores, but may have the first pores and the third pores. An example of an embodiment in which the aluminosilicate particles do not have the second pores is an embodiment in which the aluminosilicate particles are not granular. The presence or absence of third pores with a pore size of 8 nm or less can be confirmed by performing a so-called t-plot analysis of the nitrogen adsorption isotherm to confirm the presence or absence of micropores with a size of less than 2 nm, or by fitting the nitrogen adsorption isotherm using the Grand canonical Monte Carlo (GCMC) method to obtain a pore size distribution. The third pores having a pore size of 8 nm or less are, for example, possessed by acid-treated metahalloysite nanotube particles, so that, for example, when an aluminosilicate particle contains an acid-treated metahalloysite nanotube particle, the aluminosilicate particle has a third pore having a pore size of 8 nm or less. Note that general halloysite nanotube particles do not have a third pore having a pore size of 8 nm or less. The pore size of the third pores having a pore size of 8 nm or less is preferably, for example, 0.6 to 5 nm. The third pores having a pore size of 8 nm or less may have multiple peaks in the pore size distribution obtained by the above method in the region of 8 nm or less.

[0020] The aluminosilicate particles (preferably aluminosilicate granules) contained in the powder of the present invention may have pores with a pore size of more than 200 nm. The pores with a pore size of more than 200 nm may be present together with at least one of the pores with a pore size of more than 8 nm and not more than 200 nm, and the third pores with a pore size of not more than 8 nm. The presence or absence of the pores having a pore diameter of more than 200 nm can be confirmed by observing the surface of the aluminosilicate particles (preferably aluminosilicate granules) with the above-mentioned SEM. In this specification, the size (pore diameter) of the pores having a pore diameter of more than 200 nm is the diameter of the pores observed from the surface of the aluminosilicate particles (preferably aluminosilicate granules). When the shape of the pores is not a perfect circle, the maximum diameter is the pore diameter of the pores having a pore diameter of more than 200 nm. The pore diameter of the pores having a pore diameter of more than 200 nm is preferably 0.3 μm or more, more preferably 0.5 μm or more. The upper limit of the pore diameter of the pores having a pore diameter of more than 200 nm is not particularly limited, but is often 10 μm or less, and preferably 5 μm or less. The pore size of the pores having a diameter of more than 200 nm is often 99% or less, preferably 90% or less, or may be 70% or less, of the diameter (maximum diameter) of the aluminosilicate granule. The pore size of the pores having a diameter of more than 200 nm is often 1% or more, may be 5% or more, 10% or more, or may be 30% or more, of the diameter (maximum diameter) of the aluminosilicate granule.

[0021] The third pores having a pore size of 8 nm or less are nanospaces in a region close to the molecular size, and therefore can function as specific reaction sites and specific adsorption sites for molecules. When the aluminosilicate particles have third pores having a pore size of 8 nm or less, the powder of the present invention can be used, for example, as a catalyst, a catalyst carrier, an adsorbent, and the like.

[0022] In addition, the pores with a pore diameter of more than 8 nm and not more than 200 nm are a region including mesopores (2 nm or more but less than 50 nm) and macropores (50 nm or more), and are considered to have superior mass transfer properties compared to the third pores with a pore diameter of 8 nm or less, and contribute to rapid reaction and adsorption, and can be used for the same applications as those described above. Furthermore, by having the third pores with a pore diameter of 8 nm or less in combination, it is considered that even better performance can be exhibited. Since the first pores are derived from the pores of nanotube-like particles and are considered to have a tubular structure of a predetermined length, it is expected that they can also function as a catalyst with shape selectivity that selectively acts on the shape of molecules, etc. In addition, when the third pores with a pore diameter of 8 nm or less and the first pores are present, it is considered that the third pores with a pore diameter of 8 nm or less are formed on at least one of the inner wall and the outer wall of the nanotube having a tubular structure of a predetermined length, and therefore even better performance can be exhibited. The catalytic action is not limited to the surface of the aluminosilicate particles, but the diffusion inside the particles is improved and the entire aluminosilicate particle is involved in the reaction, which is expected to have effects such as improving the reaction rate and improving the durability of the catalyst. In addition, it is thought that by placing the protein serum albumin in the pores in the above region, it can be used as a synthesis site for pharmaceuticals that is similar to the environment inside the body. In addition, it can also be applied to the food industry (for example, the adsorption and removal of unnecessary proteins generated during the production process of seasonings, etc.). In addition, the pores in the mesopore region (2 nm or more and less than 50 nm) can cause molecular adsorption accompanied by liquefaction due to the capillary condensation phenomenon and can exhibit a large amount of adsorption, and therefore can function as an adsorbent (e.g., a moisture absorbent) that repeats adsorption and desorption, as well as a sustained-release material, etc.

[0023] Pores with a pore diameter of more than 200 nm are believed to contribute to the promotion of adsorption and reaction of solid substances because they allow the adsorption of larger objects. For example, when the pores have a pore diameter of more than 200 nm, it can be said that it is possible to capture dust, viruses, bacteria, pollen, etc. and react with them (for example, to inactivate them). In addition, pores with a pore diameter of more than 200 nm have excellent diffusion properties, so that they can further promote material transfer when used in the above applications.

[0024] Furthermore, the powder of the present invention may simultaneously have a third pore with a pore diameter of 8 nm or less, and a pore with a pore diameter of more than 8 nm and less than 200 nm, and may also have a pore with a pore diameter of more than 200 nm. The powder of the present invention having both of the above-mentioned pores has a novel multimodal nano-space structure, and the powder of the present invention having such a nano-space structure is expected to promote unexplored chemical reactions and has the potential to open up new technologies in the fields of the environment, energy, food, medicine, etc.

[0025] Incidentally, the above-mentioned advantages of having each of the pores are merely examples, and it goes without saying that the powder of the present invention can be applied to general uses as a porous material. The formation of each of the above pores and the adjustment of each of the pores can be adjusted by the procedure and conditions of the production method described later.

[0026] <Specific surface area> The specific surface area (BET specific surface area) of the powder of the present invention is 50 m 2 / g or more is preferable, and 100m 2 / g or more is more preferable, and 200m 2 The upper limit of the BET specific surface area is not particularly limited, but for example, 1000 m 2 / g or less, and 600m 2 / g or less in most cases. The BET specific surface area can be determined by applying the BET method to a nitrogen adsorption isotherm.

[0027] When the powder of the present invention has the above BET specific surface area, it is suitable for use as, for example, a catalyst, a catalyst support, an adsorbent, and the like. The BET specific surface area can be adjusted by the procedure and conditions of the production method described later.

[0028] <Pore volume> The total pore volume of the powder of the present invention is 0.40 cm 3 / g or more is preferable, and 0.50 cm 3 / g or more is more preferable, and 0.60 cm 3 The upper limit of the total pore volume is not particularly limited, but for example, it is 2.00 cm 3 / g or less, and 1.20 cm 3 / g or less in most cases. The total pore volume is calculated from the adsorption amount at a relative pressure of 0.99 from the nitrogen adsorption isotherm using the following formula. Vp = V / 22414 × Mg / ρg Vp: total pore volume up to relative pressure (0.99) V: Adsorption amount at relative pressure (0.99) 22414:Volume of gas per mole Mg: Molecular weight of adsorbate (N2) (28.013) ρg: Density of the adsorbate (N2) (0.808)

[0029] When the powder of the present invention has the above total pore volume, it is suitable for use as, for example, a catalyst, a catalyst support, an adsorbent, a sustained release material, and the like. The total pore volume can be adjusted by the procedure and conditions of the production method described later.

[0030] In addition, when the powder of the present invention has micropores (less than 2 nm), the volume of the micropores is less than 0.01 cm 3 / g or more is preferable, and 0.02 cm 3 / g or more is more preferable, and 0.04 cm 3 / g or more is more preferable, and 0.08 cm 3 The upper limit of the volume of the micropores is not particularly limited, but is, for example, 0.5 cm 3 / g or less, and 0.2 cm 3 / g or less in most cases. The micropore volume is determined by t-plot analysis. The volume of the micropores can be adjusted by the procedure and conditions of the production method described later.

[0031] <Water vapor adsorption amount> The water vapor adsorption amount of the powder of the present invention is 120 cm at a relative pressure of 0.9. 3 / g or more is preferable, and 200 cm 3 / g or more is more preferable, and 300 cm 3 The upper limit of the water vapor adsorption amount is not particularly limited, but for example, it is 2000 cm at a relative pressure of 0.9. 3 / g or less, and 1000cm 3 / g or less in most cases. The amount of water vapor adsorption at a relative pressure of 0.9 is obtained from the adsorption isotherm of water vapor at 25°C.

[0032] When the powder of the present invention has the above water vapor adsorption amount, it is suitably used, for example, as a catalyst, a catalyst carrier, a humidity conditioner, a sustained release material, etc. It is also suitably used as an adsorbent utilizing its hydrophilicity. The amount of water vapor adsorption can be adjusted by the procedure and conditions of the production method described later.

[0033] <Toluene vapor adsorption amount> The toluene vapor adsorption amount of the powder of the present invention is 40 cm at a relative pressure of 0.9. 3 / g or more is preferable, and 50 cm 3 / g or more is more preferable, and 60 cm 3 The upper limit of the toluene adsorption amount is not particularly limited, but for example, 200 cm at a relative pressure of 0.9. 3 / g or less, and 150 cm 3 / g or less in most cases. The amount of toluene vapor adsorption at a relative pressure of 0.9 was obtained from the adsorption isotherm of toluene vapor at 25°C.

[0034] When the powder of the present invention has the above-mentioned toluene vapor adsorption amount, it is suitably used, for example, as a catalyst, a catalyst carrier, an adsorbent, and the like. The amount of toluene vapor adsorption can be adjusted by the procedure and conditions of the production method described later.

[0035] <Solid acid amount> The amount of NH3 desorption from the powder of the present invention at 400° C. or higher measured by a temperature programmed desorption method is preferably 4 μmol / g or more, more preferably 5 μmol / g or more, and even more preferably 10 μmol / g or more. There is no particular upper limit to the amount of NH3 desorption, but it may be, for example, 1000 μmol / g or less, and is often 500 μmol / g or less. The amount of NH3 desorption at 400° C. or higher by the temperature programmed desorption method can be obtained by measurement at 100 to 800° C. The detailed measurement method is as described in the Examples section below. The amount of NH3 desorbed at temperatures above 400°C using the temperature programmed desorption method is considered to correspond to the amount of solid acid with a relatively high acid strength.

[0036] When the powder of the present invention has the above-mentioned amount of NH3 desorption, it can be suitably used as, for example, a catalyst that utilizes a solid acid, a catalyst support, a dual-function catalyst, an adsorbent, and the like. In addition, when the powder of the present invention contains aluminosilicate granules, it can be said that the powder of the present invention can be easily applied to catalytic reactions using a flow method. The amount of NH3 released can be adjusted by the procedure and conditions of the production method described later.

[0037] <Amount of methylene blue adsorbed> The methylene blue adsorption amount of the powder of the present invention is preferably 40 mg / g or more, more preferably 50 mg / g or more, and even more preferably 60 mg / g or more. There is no particular upper limit to the methylene blue adsorption amount, but it can be, for example, 200 mg / g or less, and is often 100 mg / g or less. The above methylene blue adsorption amount indicates the amount of methylene blue adsorbed per gram of the powder of the present invention. The amount of methylene blue adsorbed per gram of powder is calculated from the concentration of the methylene blue solution before it comes into contact with the powder (pre-contact concentration), the concentration of the methylene blue solution obtained after stirring the powder and methylene blue solution overnight and then separating the solid-liquid components using a centrifuge (post-contact concentration), the amount of methylene blue solution used, and the amount of powder added. The concentration of methylene blue is measured from the absorbance at 664.5 nm.

[0038] When the powder of the present invention has the above-mentioned adsorption amount of methylene blue, it can be suitably used, for example, as an adsorbent for dyes and cationic ions. The amount of methylene blue adsorbed can be adjusted by the procedure and conditions of the production method described later.

[0039] <Metahalloysite nanotube particles> The metahalloysite nanotube particles that may be contained in the above-mentioned aluminosilicate particles refer to nanotube-shaped halloysite in which the OH of halloysite represented by Al2Si2O5(OH)4 has been dehydrated to give a low crystallinity, and metahalloysite has traditionally been used commonly or conventionally as a term representing a variant of halloysite. The metahalloysite nanotube particles are obtained by firing the halloysite nanotube particles at a predetermined temperature. The predetermined temperature is preferably 600° C. or higher. The upper limit of the predetermined temperature is preferably 925° C. or lower, more preferably 900° C. or lower.

[0040] <Acid-treated metahalloysite nanotube particles> In this specification, the acid-treated metahalloysite nanotube particles refer to those obtained by subjecting metahalloysite nanotube particles to acid treatment as described above. In the acid-treated metahalloysite nanotube particles, the content of Al2O3 is often reduced by acid treatment compared to before the acid treatment, and for example, aluminosilicate particles containing acid-treated metahalloysite nanotube particles are likely to satisfy the above-mentioned SiO2 / Al2O3 requirements. In the acid-treated metahalloysite nanotube particles, pores other than the pores corresponding to the inner diameter of the halloysite nanotube particles are often generated by the acid treatment. The acid-treated metahalloysite nanotube particles preferably have a third pore having a pore diameter of 8 nm or less.

[0041] FIG. 1 shows a transmission electron microscope (TEM) image of metahalloysite nanotube particles (before acid treatment, SiO2 / Al2O3=2.0, calcined at 900°C), and FIG. 2 shows a TEM image of acid-treated metahalloysite nanotube particles (SiO2 / Al2O3=6.3, dried at 110°C). In the metahalloysite nanotube particles (FIG. 1), the contrast difference is not large in the wall portion constituting the tube, and it can be seen that the thickness of the wall constituting the tube is uniform. On the other hand, in the acid-treated metahalloysite nanotube particles (FIG. 2), a clear contrast difference is observed in the wall portion constituting the tube, and the parts that are close to white in color in FIG. 2 can be said to correspond to voids where nothing exists, so it is considered that they have pores (third pores with a pore diameter of 8 nm or less) (see the examples in the following section). The above TEM images were taken using a JEOL "JEM-ARM200F" equipped with a cold-cathode field emission electron gun (Cold-FEG) at an accelerating voltage of 20 kV.

[0042] Furthermore, as a result of the inventor's investigations, it was found that the physical properties of the acid-treated metahalloysite nanotube particles obtained change depending on the firing temperature when the metahalloysite nanotube particles are obtained. The firing temperature of the metahalloysite nanotube particles is preferably within the above-mentioned range, and can be appropriately adjusted according to the desired physical properties of the powder. In addition, the conditions of the acid treatment when obtaining the acid-treated metahalloysite nanotube particles can be appropriately adjusted according to the physical properties of the desired powder. The physical properties such as the specific surface area of ​​the powder of the present invention including the aluminosilicate particles including the acid-treated metahalloysite nanotube particles can be appropriately adjusted by the temperature of the acid treatment, the time of the acid treatment, the type of acid used, the concentration of the acid, and the amount of the treated powder relative to the acid. The physical properties of the powder can also be adjusted by the number of times of acid treatment. For example, by repeating the acid treatment, the SiO2 / Al2O3 can be increased. Furthermore, the acid-treated metahalloysite nanotube particles may be further subjected to a calcination treatment after the acid treatment. The calcination treatment can also adjust the physical properties of the powder of the present invention, such as the specific surface area. The calcination treatment can also adjust the moisture content of the powder of the present invention. For details regarding the relationship between the conditions such as the acid treatment conditions and the physical properties such as the specific surface area of ​​the powder of the present invention, please refer to the production method and examples described later.

[0043] <Other components and other particles> In the powder of the present invention, the aluminosilicate particles may contain components other than the nanotube particles. For example, the aluminosilicate particles may include a catalytic component that drives a desired reaction. The catalytic component may be supported on the aluminosilicate granules or nanotube particles as particles, or as clusters of single atoms or a few atoms. The catalytic component may also be supported on the aluminosilicate granules and nanotube particles. The elements contained in the catalyst component are not particularly limited and can be selected according to the desired reaction. Examples of elements contained in the catalyst component include Group 1 elements to Group 17 elements, and often contain transition metal elements or rare earth elements. The type of element contained in the catalyst component may be one type, or two or more types. The above-mentioned catalyst component is a concept that includes not only a catalyst component that advances a desired reaction, but also a so-called co-catalyst that promotes the progress of the desired reaction. The catalyst component may be a known one, and the catalyst component may be supported by a known method.

[0044] In the powder of the present invention, the aluminosilicate particles may contain a medicinal component as a component other than the nanotube particles. The medicinal component is not particularly limited, and examples thereof include known deodorant components, antibacterial components, germicidal components, and pharmaceutical components.

[0045] Furthermore, the aluminosilicate particles (preferably aluminosilicate granules) may contain particles (other particles) other than the nanotube particles, as described above. The other particles are not particularly limited, and examples thereof include magnetic particles, coloring material particles, and drug particles, etc. For example, when the aluminosilicate granules contain magnetic particles, the aluminosilicate granules can be collected by magnetic force.

[0046] <Powder characteristics> The average particle size of the powder of the present invention is not particularly limited and may be appropriately selected depending on the application, but is, for example, 0.5 to 200 μm, preferably 1 to 100 μm. The powder of the present invention may be granulated before use. The size of the granulated powder is preferably 5 mm or less. The granulated powder may be subjected to at least one of crushing and pulverization to adjust the average particle size. The average particle size is measured using a laser diffraction / scattering particle size distribution analyzer (Microtrac MT3300EXII) manufactured by Microtrac Bell.

[0047] The powder of the present invention preferably has a breaking strength of 5.0 MPa or more for the aluminosilicate particles (preferably aluminosilicate granules). When the aluminosilicate particles (preferably aluminosilicate granules) contained in the powder of the present invention have the above breaking strength, the pores (e.g., the first pores and the second pores, particularly the second pores) having a pore size of more than 8 nm and not more than 200 nm are easily maintained. Therefore, when the aluminosilicate particles (preferably aluminosilicate granules) contained in the powder of the present invention have the above breaking strength, they are not easily broken during handling, pretreatment (e.g., dispersion treatment), and composite treatment (e.g., kneading with resin), and the like, and the pores can be maintained. On the other hand, the breaking strength of the particles of general porous materials such as so-called silica gel, mesoporous silica, and activated carbon is often small, and the particles are broken during the above operations, etc., and the pore structure may not be maintained. The breaking strength is more preferably 6.0 MPa or more, and even more preferably 7.0 MPa or more. The upper limit of the breaking strength is not particularly limited, and is, for example, 60.0 MPa or less, preferably 50.0 MPa or less, and more preferably 45.0 MPa or less.

[0048] The breaking strength of the aluminosilicate particles (preferably aluminosilicate granules) is measured by a compression test using a microcompression tester, and is the average value of five test results. More specifically, first, the powder of the present invention (aluminosilicate particles (preferably aluminosilicate granules)) is used as a sample. A very small amount of this sample is scattered on the sample stage (lower pressure plate) of a micro-compression tester MCT-510 (manufactured by Shimadzu Corporation), and a compression test is performed on each sample particle to determine the breaking strength. Usually, the average value of five test results (breaking strength) is taken as the breaking strength of the powder. The breaking strength is calculated by measuring the diameters of each sample particle in the X and Y directions on the sample stage, taking the average value as the particle size of each sample particle, and using the following formula (1). (1) Cs = 2.48 × P / (πd 2 ) In formula (1), Cs is the breaking strength (unit: MPa), P is the breaking test force (unit: N), and d is the diameter of the sample particle (unit: mm).

[0049] In addition, it is also preferable that the powder of the present invention has a hydrous breaking strength of 80% or more of the above breaking strength when the aluminosilicate particles (preferably aluminosilicate granules) are immersed in pure water for 24 hours to be hydrous. The hydrous breaking strength may be the same value as the above breaking strength, i.e., 100%. When the hydrous breaking strength is excellent, the pore structure is easily maintained even in applications where the powder comes into contact with aqueous solutions, etc., which is preferable. The wet fracture strength is measured in the same manner as in the above-mentioned method for measuring fracture strength, except that the sample is aluminosilicate particles (preferably aluminosilicate granules) that have been immersed in pure water for 24 hours to become wet.

[0050] [Powder applications] The powder of the present invention can be used in a wide variety of applications. In addition to the above-mentioned applications, examples of the applications include cosmetics, coloring materials, precision polishing particles, magnetic materials, deodorants, antibacterial agents, water purification agents, food, fermentation, pharmaceuticals, and artificial enzymes, but needless to say, the applications are not limited to these. In addition, the powder of the present invention is also suitable as a filler or coating material that imparts properties such as light weight, heat insulation, or sound absorption.

[0051] [Powder manufacturing method] In the method for producing a powder of the present invention, a powder containing aluminosilicate particles is calcined at 600 to 900°C to obtain a calcined powder, and the calcined powder is subjected to an acid treatment. The aluminosilicate particles contain nanotube particles, and the molar ratio of the SiO2 content to the Al2O3 content is less than 2.1. The molar ratio of the SiO2 content to the Al2O3 content is often 1.8 or more, and may be 1.9 or more. Hereinafter, the process of obtaining fired powder by firing at 600 to 900° C. is also referred to as the “firing process”, and the process of subjecting the fired powder to an acid treatment is also referred to as the “acid treatment process”. In addition, hereinafter, the powder containing the aluminosilicate particles to be subjected to the firing step is also referred to as "unfired powder." Furthermore, the aluminosilicate particles containing nanotube particles contained in the unfired powder are also referred to as "unfired particles." Preferred and alternative procedures for the method of producing the powder of the present invention are described below.

[0052] The unsintered particles preferably contain nanotube particles as primary particles. The method of obtaining the unsintered powder (unsintered particles) is not particularly limited. For example, the powder containing nanotube particles may be crushed or pulverized to an appropriate size to obtain the unsintered powder. Alternatively, the solvent component may be removed from the slurry containing nanotube particles by drying to obtain a molded body, and the molded body may be crushed to an appropriate size to obtain the unsintered powder, or the slurry may be dried to obtain the unsintered powder. Alternatively, the slurry containing nanotube particles may be spray-dried to obtain the unsintered powder (unsintered granules). Alternatively, the slurry containing nanotube particles may be subjected to medium-fluid drying or freeze-drying to obtain the unsintered powder (unsintered granules). In particular, it is preferable to perform a spray drying process on a slurry containing nanotube particles to obtain an unsintered powder, since this makes it easier to obtain the powder of the present invention having second pores corresponding to the interparticle voids of the nanotube particles described above. That is, the method for producing a powder of the present invention preferably includes a spray drying step of subjecting a slurry containing nanotube particles to a spray drying process to obtain an unsintered powder. The nanotube particles preferably include halloysite nanotube particles. Note that the embodiment of the spray drying step described below is an embodiment in which the nanotube particles include halloysite nanotube particles.

[0053] The spray drying process includes a slurry preparation step of obtaining a slurry containing nanotube particles, and a powder preparation step of carrying out spray drying. In the slurry preparation step, for example, a slurry containing water and nanotube particles (halloysite nanotube particles) is obtained. An example of the powder preparation step is a step of obtaining a powder by spray drying the slurry prepared in the slurry preparation step. The means for preparing powder from the above slurry is not limited to spray drying, and may be, for example, fluidized bed drying (ball-containing fluidized bed drying). Suitable methods for obtaining the unsintered powder include, for example, the methods described in paragraphs

[0011] to

[0029] of WO 2018 / 079556.

[0054] By adjusting the procedure and conditions for obtaining the unsintered powder, the particle size of the unsintered granules in the obtained unsintered powder can be adjusted. The average particle size of the unsintered powder is preferably 0.5 to 200 μm. The average particle size of the unsintered powder can be adjusted depending on the purpose, and methods for adjusting the average particle size include crushing and pulverization.

[0055] <Firing process> In the powder production method of the present invention, the unsintered powder is sintered at 600 to 900° C. to obtain a sintered powder. It is believed that the nanotube particles contained in the aluminosilicate particles are modified by firing at such a firing temperature. When halloysite nanotube particles are used as the nanotube particles, it is believed that the crystal water in the halloysite nanotube particles is eliminated and the particles are changed to metahalloysite nanotube particles. In this case, the shape of the tubes is often not changed. Furthermore, when aluminosilicate granules are used as the aluminosilicate particles, firing at such a firing temperature increases the strength and makes it easier to maintain the granular structure before firing.

[0056] The above-mentioned slurry may contain a surfactant to adjust the dispersion state and viscosity, and may contain template particles made of an organic material to form pores with a pore size of more than 200 nm. When the slurry contains the above-mentioned components, the above-mentioned components may remain in the uncalcined powder obtained by spray drying or the like. However, these organic substances can be removed by calcining the powder in an air atmosphere or the like.

[0057] The firing temperature can be adjusted appropriately depending on the desired physical properties of the powder obtained. From the viewpoint of obtaining a powder with a larger SiO2 / Al2O3, the firing temperature is preferably 800 to 900°C. By setting the firing temperature within the above range, Al2O3 is easily leached in the subsequent acid treatment step, and SiO2 / Al2O3 tends to increase (see the examples later). In addition, the above physical properties can be controlled by the degree of SiO2 / Al2O3 (see the examples later).

[0058] The firing time is not particularly limited and is, for example, 0.5 to 4 hours, preferably 1 to 2 hours. The firing atmosphere is not particularly limited, and may be, for example, an air atmosphere, a nitrogen atmosphere, etc., with the air atmosphere being preferred. The firing atmosphere may also be an atmosphere with a higher oxygen content than the air atmosphere. As described above, when the firing atmosphere is an air atmosphere or an atmosphere with a higher oxygen content than the air atmosphere, it is easy to remove template particles composed of surfactants and organic substances. The average particle size of the fired powder is preferably 0.5 to 200 μm. The average particle size of the fired powder can be adjusted depending on the purpose, and examples of the method for adjusting the average particle size include a crushing process and a grinding process.

[0059] <Acid treatment process> In the powder production method of the present invention, the calcined powder is subjected to an acid treatment. When the calcined powder is subjected to an acid treatment, the Al2O3 component is mainly leached from the aluminosilicate particles including nanotube particles, and the above-mentioned powder of the present invention (powder including aluminosilicate particles in which the molar ratio of the SiO2 content to the Al2O3 content is 2.1 or more) is obtained. The acid treatment refers to a treatment in which the calcined powder is brought into contact with an acid treatment liquid. Here, the external shape of the nanotube shape is hardly changed by the acid treatment (see Figures 1 and 2). The inventors have found that Al2O3 is not easily leached even if aluminosilicate particles containing nanotube particles are subjected to an acid treatment step without undergoing a calcination step. The mechanism behind this is not entirely clear, but is speculated as follows. That is, although nanotube particles (halloysite nanotube particles) are relatively stable against acid, when they undergo a calcination step, the crystal water in the nanotube particles (halloysite nanotube particles) is eliminated and they become amorphous. At this time, although no change is observed in the overall shape of the nanotube particles, the coordination number of Al changes, and in particular five-coordinated Al is generated, which is thought to make it easier for the Al component to be leached by acid. In order to verify the above hypothesis, measurements were carried out using solid-state nuclear magnetic resonance (Solid-state Nuclear Magnetic Resonance) ( 27 Al (DDMAS method), it was confirmed that a peak corresponding to five-coordinate Al, which was hardly observed before the calcination process, appeared in the aluminosilicate particles that had undergone the calcination process. Furthermore, it was confirmed that the peak corresponding to the above-mentioned five-coordinate Al was preferentially decreased after the acid treatment process.

[0060] The acid treatment liquid used in the acid treatment is preferably a liquid containing water and an acidic component, that is, an acidic aqueous solution. The acid treatment liquid may be a conventionally known acid aqueous solution, for example, inorganic acids such as hydrochloric acid, nitric acid, sulfuric acid, and phosphoric acid, and organic acids such as oxalic acid and acetic acid. The acid treatment liquid may contain two or more acids. That is, the acid treatment liquid may be a mixed acid. The concentration of the acid in the acid treatment solution is not particularly limited as long as the desired amount of Al2O3 is leached, but is preferably 0.1 mol / L or more, more preferably 1.0 mol / L or more, and even more preferably 2.0 mol / L or more in terms of shortening the acid treatment time. The upper limit of the acid concentration in the acid treatment solution is not particularly limited, but is, for example, 12.0 mol / L or less. The type of acid contained in the acidic treatment solution can be appropriately selected depending on the desired physical properties, cost, and the like. In addition, it is preferable to select materials that are resistant to corrosion by the acid contained in the acid treatment solution for the parts of the equipment for carrying out the acid treatment that may come into contact with the acid treatment solution.

[0061] In the acid treatment, the method of contacting the calcined powder with the acid treatment liquid includes, for example, putting the calcined powder in the acid treatment liquid and stirring the acid treatment liquid. In the acid treatment, it is preferable that the calcined powder is dispersed in the acid treatment liquid in order to more uniformly leach Al2O3 from the aluminosilicate particles. The stirring method is not particularly limited, and for example, the acid treatment liquid and the calcined powder may be placed in a tank equipped with a stirring blade and stirred. Stirring makes it easy to maintain the dispersion state of the calcined powder in the acid treatment liquid. The dispersion state of the calcined powder may also be maintained by shaking. The ratio of the mass of the acid treatment liquid to the mass of the calcined powder can be appropriately set, but may be, for example, 5 to 100, and preferably 10 to 50. When the ratio is large, leaching of Al2O3 tends to be promoted. The temperature of the acid treatment solution during the acid treatment can be appropriately set, for example, to 10 to 100° C., and preferably 20 to 90° C. When the temperature of the acid treatment solution during the acid treatment is increased, leaching of Al2O3 tends to be promoted. The time for the acid treatment can be appropriately adjusted depending on the desired SiO2 / Al2O3 and the above-mentioned desired physical properties, as well as the type of acid treatment liquid used, the ratio of the mass of the acid treatment liquid to the mass of the fired powder, and the temperature of the acid treatment liquid, and is, for example, 10 minutes to 48 hours, and preferably 30 minutes to 12 hours. The acid treatment step is also preferably carried out in an apparatus equipped with a cooler for cooling and refluxing the evaporated acid treatment liquid.

[0062] In the acid treatment step, impurity components other than Al2O3 contained in the aluminosilicate particles (for example, Fe2O3, CaO, MgO, K2O, Na2O, etc.) may be leached.

[0063] When aluminosilicate granules containing halloysite nanotube particles are used as the unsintered granules contained in the unsintered powder to be subjected to the powder manufacturing method of the present invention, aluminosilicate granules containing acid-treated metahalloysite nanotube particles as primary particles are obtained through the firing step and the acid treatment step. As described above, the acid-treated metahalloysite nanotube particles often have third pores with a pore size of 8 nm or less. Surprisingly, even when the halloysite nanotube particles are subjected to a calcination step and an acid treatment step to obtain acid-treated metahalloysite nanotube particles, the pores derived from the halloysite nanotube particles are maintained (see the examples below). Furthermore, in the powder production method of the present invention, the pores derived from the interparticle voids of the nanotube particles confirmed before the calcination step and the acid treatment step are maintained (see the examples below). That is, in the powder production method of the present invention, the first pores corresponding to the tube pores of the halloysite nanotube particles and the second pores derived from the interparticle voids of the nanotube particles confirmed before the calcination step and the acid treatment step are maintained.

[0064] <Cleaning process> The method for producing a powder of the present invention may include a step of washing the obtained powder (washing step). The washing step is preferably performed between the acid treatment step and the post-calcination step described below, or between the acid treatment step and the drying step described below. The washing step makes it possible to remove the acid treatment solution in which Al2O3 has been dissolved, and the like, from the obtained powder. The washing step is preferably a step of contacting the obtained powder with a washing liquid. The washing liquid may be, for example, water. The water is preferably purified water (e.g., distilled water, ion-exchanged water, reverse osmosis water, etc.).

[0065] The method for contacting the obtained powder with the washing liquid may be the same as that for the acid treatment step. After contacting with the washing liquid, the powder is separated from the washing liquid. The separation method is not particularly limited, and any known method can be applied, for example, sedimentation separation, filtration separation, and the like. Sedimentation separation utilizes gravity or centrifugal force to separate liquid and powder due to the difference in specific gravity. In filtration separation, the powder is separated from the liquid by trapping the powder in a filter or the like and passing the liquid through the filter. Filtration separation may be dead-end filtration or cross-flow filtration.

[0066] The washing step may be carried out repeatedly. For example, after the powder is separated from the washing liquid by the above method, the separated powder is again brought into contact with the washing liquid and the washing step is repeated. The washing step may be repeated, for example, until the conductivity of the filtrate reaches a predetermined level.

[0067] <Drying process> In the method for producing a powder of the present invention, it is preferable to carry out a drying treatment on the obtained powder (for example, the powder obtained in the acid treatment step or the powder obtained in the washing step). The drying method is not particularly limited, and known methods such as stationary drying and fluidized drying can be applied. In addition, spray drying, fluidized bed drying, freeze drying, etc. may be applied to the slurry containing the powder. The above method can be applied even when it is difficult to separate the slurry into solid and liquid. In addition, according to the above method, the powder can be obtained directly from the slurry. The drying temperature is usually 200° C. or lower.

[0068] <Post-firing process> The powder producing method of the present invention may further include a step of calcining the obtained powder (e.g., the powder obtained in the acid treatment step, the powder obtained in the washing step, or the powder obtained in the drying step) (a post-calcination step). The specific method of firing can be the same as that of the firing step described above. The firing temperature in the post-firing step is preferably more than 200° C. and not more than 1100° C., more preferably 300 to 1000° C. The preferred embodiment of the firing atmosphere is the same as that of the firing step described above. In the post-firing process, the above-mentioned physical properties of the powder can be adjusted by the firing temperature (see the examples below). For example, it has been found that the values ​​of the above-mentioned physical properties tend to decrease when the temperature of the post-firing process is increased. Therefore, the above-mentioned physical properties can be controlled to desired values ​​by adjusting the conditions of each of the above-mentioned processes and the firing temperature of the post-firing. In addition, by carrying out post-firing, it is possible to impart heat resistance up to the temperature range in which the post-firing is carried out. For example, if the temperature of the post-firing is set higher than the environment in which the powder of the present invention is used, it is expected that the powder of the present invention will be less likely to denature when used and will have improved durability. Therefore, it is also preferable to select the temperature of the post-firing depending on the environment in which the powder of the present invention is used.

[0069] It should be noted that, when the post-calcination process is performed, although the physical properties change as described above, the pores (first pores) originating from the nanotube particles, the pores (second pores) originating from the interparticle voids of the nanotube particles, and the third pores with a pore size of 8 nm or less possessed by the acid-treated metahalloysite nanotube particles are often maintained (see the examples below).

[0070] In the method for producing a powder of the present invention, it is also preferable to mix particles (template particles) of a material that disappears in the firing step or the acid treatment step with the slurry to be subjected to the spray drying step. When the slurry containing the template particles is subjected to the spray drying step, aluminosilicate granules containing template particles and nanotube particles are obtained. When the powder containing such aluminosilicate granules is subjected to the firing step and the acid treatment step, the template particles are removed and pores (e.g., pores with a pore diameter of more than 200 nm) corresponding to the shape of the template particles are generated. By adjusting the size, shape, and amount of the template particles, as well as the spray drying conditions, it is possible to generate pores of a desired shape (e.g., pores with a pore diameter of more than 200 nm). The template particles of the material that disappears in the firing step are not particularly limited, but examples thereof include resin particles, carbon particles, etc. Furthermore, the template particles of the material that disappears in the acid treatment step are not particularly limited, but examples thereof include magnesium oxide particles, calcium carbonate particles, zinc oxide particles, etc. EXAMPLES

[0071] The present invention will be specifically described below with reference to examples, although the present invention is not limited to the following examples.

[0072] [Unfired powder] The unsintered powder to be subjected to the sintering step was obtained by the following procedure.

[0073] <Raw material halloysite> Halloysite manufactured by APPLIED MINERALS (product name: DRAGONITE-HP) was used as the raw material halloysite.

[0074] <Slurrying> Raw halloysite, water and anionic polymer surfactant (Poise 532A, Kao Corporation) were placed in a high-speed mixer (Ultra Homo Mixer UHM-20 (20 liters), manufactured by Nippon Seiki Seisakusho Co., Ltd.) and processed at 10,000 rpm for 10 minutes to obtain a slurry (solid content concentration: 40% by mass) in which raw halloysite was dispersed in water. The content of the anionic polymer surfactant was 1.9% by mass relative to the total solid content of the slurry.

[0075] <Centrifugation> The slurry was allowed to settle naturally for 2 hours to remove coarse particles, and the slurry from which the coarse particles had been removed was then centrifuged at a centrifugal force of 2500G for 10 minutes using a centrifuge (Model 7000, high-speed, large-capacity refrigerated centrifuge, manufactured by Kubota Shoji Co., Ltd.) to separate the slurry into a settled phase containing impurities such as quartz and coarse particles, and a dispersed phase containing suspended fine particles including nanotubes.

[0076] <Spray drying> A dispersed phase (slurry) containing nanotubes and having a solid content concentration of 25.1% was spray-dried using a spray dryer to obtain a powder (unfired powder) of aluminosilicate particles (aluminosilicate granules) having an average particle size of 6.0 μm. The spray dryer used was an L-8i spray dryer manufactured by Okawara Kakoki Co., Ltd. The slurry was pumped into the drying chamber at a fixed rate to atomize (spray) and dry the slurry. The contact method between the hot air and the sprayed droplets was a parallel flow type where both the hot air and the sprayed droplets flowed downward. The spray drying conditions are as follows: Atomization method: Four-fluid nozzle method Spray air pressure: 0.20MPa Slurry supply rate: 2.6kg / h ·Inlet temperature: 190℃ ·Outlet temperature: 88℃ The unsintered powder was a powder containing aluminosilicate granules containing halloysite nanotube particles as primary particles. In the following examples, the unsintered powder obtained by the above procedure (also referred to as "unsintered powder 1") was used as the unsintered powder.

[0077] [Relationship between the firing temperature in the firing process and the amount of Al2O3 leaching] Unsintered powder 1 was sintered at each temperature shown in Table 1 below to obtain sintered powder (sintering step). For sintering, an electric furnace with a siliconite heating element was used, and the temperature was increased at a rate of 4°C / min, and the temperature shown in Table 1 below was held for 1 hour, and then the furnace was cooled. The XRD charts of each calcined powder and uncalcined powder are shown in Figure 3. In Figure 3, the uncalcined powder is described as "uncalcined," and each calcined powder is described by its calcination temperature. As can be seen from Figure 3, only the crystalline phase of halloysite was observed in the unsintered powder. When fired at 600°C, the half-width of each diffraction peak increased, indicating low crystallinity. At 800°C and 900°C, almost no diffraction peaks were observed, indicating amorphization. On the other hand, at 950°C and 1000°C, it can be seen that γ-Al2O3 was formed.

[0078] The measurement conditions for obtaining the XRD chart shown in FIG. 3 are as follows: Equipment used: X-ray diffraction analyzer D8ADVANCE (manufactured by BRUKER) Measurement X-ray: CuKα Tube voltage: 35kV ·Tube current: 40mA ·Optical system: Concentration method Detector: One-dimensional semiconductor detector Scan range: 2~70deg Scan step: 0.021deg Scan speed: 4deg / min

[0079] The SiO2, Al2O3 and Fe2O3 contents of each of the obtained sintered powders were determined by the above-mentioned XRF method, and the SiO2 / Al2O3 ratio was calculated by the above-mentioned method. Note that the SiO2, Al2O3 and Fe2O3 contents are normalized to 100% without including the ignition loss equivalent to moisture. In addition, the BET specific surface area and total pore volume of each of the obtained sintered powders were measured. The detailed measurement conditions are as described below. The measurement results of the calcined powder before the acid treatment are shown in Table 1.

[0080] Next, each of the fired powders and the unfired powder shown in Table 1 was subjected to an acid treatment. The acid treatment was performed using hydrochloric acid (acid treatment liquid) with the following concentration. The calcined or uncalcined powder and the acid treatment liquid were placed in a glass beaker, and the mixture was stirred with a PTFE stirring blade. The acid treatment was performed by heating the glass beaker with a mantle heater and controlling the liquid temperature to the following temperature. After the acid treatment, suction filtration was performed to separate the solid and liquid, and then a process of dispersing the product in ion-exchanged water and a process of performing solid-liquid separation (washing process) were repeatedly performed using ion-exchanged water until the conductivity of the filtrate reached the following value. After the washing process, the mixture was dried at 110°C to obtain a powder. The powders thus obtained were subjected to the same measurements as those for the sintered powders. The measurement results for each of the powders thus obtained are shown in Table 2.

[0081] <Acid treatment conditions> Acid treatment solution: 2mol / L hydrochloric acid Liquid temperature: 60℃ Duration: 2 hours Ratio of mass of acid treatment solution to mass of calcined or uncalcined powder (acid treatment solution / powder): 25 Filtrate conductivity at the end of washing: 1mS / m

[0082] [Table 1]

[0083] [Table 2]

[0084] From the results in Table 2, when the unsintered powder was subjected to acid treatment, the SiO2 / Al2O3 ratio did not change. In addition, the BET specific surface area and total pore volume also showed little change before and after the acid treatment. On the other hand, the powder obtained by firing at 600 to 900°C and then treating with acid (the powder of the present invention) had an increased SiO2 / Al2O3 ratio, and it was also confirmed that the BET specific surface area and total pore volume were also significantly increased. On the other hand, the SiO2 / Al2O3 ratio did not change in the powders obtained by calcining at 950℃ and 1000℃ and then performing acid treatment. In addition, the BET specific surface area and total pore volume also showed little change before and after the acid treatment. It was also confirmed that the Fe2O3 content was reduced in the powder obtained by firing at 600 to 900°C and then performing an acid treatment.

[0085] If the mass reduction due to the acid treatment is taken as the amount of Al2O3 dissolved into the acid treatment solution, it was confirmed that the amount of Al2O3 reduction calculated from the Al2O3 content in each powder measured by XRF roughly coincided with the amount of Al2O3 dissolved, and therefore it is believed that the Al2O3 component is mainly leached in the acid treatment.

[0086] <Nitrogen adsorption isotherm> In the present invention, nitrogen adsorption isotherms were obtained under the following conditions and procedures, and various analyses were carried out. First, the powder was pretreated, and then the adsorption and desorption isotherms with nitrogen were measured using a constant volume method under the following conditions: The equilibrium waiting time is the waiting time after the adsorption equilibrium state is reached. ·Adsorption temperature: 77K Cross section of nitrogen: 0.162nm 2 Saturated vapor pressure: Actual measurement Equilibration wait time: Until the pressure change over 500 seconds is within 0.2% of the pressure gauge reading Pretreatment device: BELPREP-vacII (Microtrack, BEL) Measurement device: BELSORP-MaxII (Microtrack BEL) Analysis software: BELMaster Version 6.4.0.0 (Microtrack-Bell) For samples fired at 500°C or higher, the pretreatment was a vacuum degassing treatment at 300°C for 8 hours, while for samples fired at less than 500°C, the pretreatment was a vacuum degassing treatment at 170°C for 3.5 hours.

[0087] BET specific surface area [m 2 / g] was determined by applying the BET method to the nitrogen adsorption isotherm. Total pore volume [cm 3 / g] was determined by the method described above. The pore volume distribution from about 2.6 nm to about 200 nm was determined from the nitrogen adsorption isotherm by applying the BJH method using the FHH standard curve.

[0088] [Relationship between acid treatment conditions and amount of Al2O3 leached] The sintered powder (SiO2 / Al2O3=2.0) in which the sintering temperature in the above sintering step was set at 900°C was subjected to acid treatment under different acid treatment conditions. Specifically, the acid treatment was performed by changing the concentration of hydrochloric acid in the acid treatment solution and the temperature of the acid treatment solution so as to correspond to the plots in Fig. 4. The treatment time was 2 hours, the mass ratio of the acid treatment solution to the mass of the fired powder was 25, and the acid treatment was performed in the same manner as described above. FIG. 4 is a graph showing the relationship between the acid treatment temperature and SiO2 / Al2O3 after the acid treatment.

[0089] As shown in Figure 4, it was confirmed that the SiO2 / Al2O3 in the obtained powder can be adjusted by adjusting the acid treatment conditions. In addition, as shown in the results in the latter section, each physical property can be adjusted by adjusting the SiO2 / Al2O3.

[0090] [Relationship between SiO2 / Al2O3 and BET specific surface area] As described above, the SiO2 / Al2O3 ratio can be controlled by adjusting the acid treatment conditions. That is, the SiO2 / Al2O3 ratio of the powder obtained can be controlled by adjusting various conditions in the acid treatment, such as the acid concentration and temperature. It can also be understood that the SiO2 / Al2O3 ratio of the powder obtained can be controlled by the acid treatment time and the mass ratio of the acid treatment solution to the mass of the fired powder. Figure 5 shows the relationship between SiO2 / Al2O3 and the BET specific surface area of ​​the powder produced by adjusting the acid treatment conditions for the sintered powder (SiO2 / Al2O3=2.0) with the sintering temperature set at 900°C in the above sintering process. The powder data shown in Figure 5 was obtained by measuring the powder obtained by adjusting the SiO2 / Al2O3 by the acid treatment conditions and washing and drying (110°C) in the same manner as above.

[0091] From the results shown in Fig. 5, it can be seen that the BET specific surface area changes according to SiO2 / Al2O3. That is, it can be understood that the BET specific surface area can be adjusted by adjusting SiO2 / Al2O3.

[0092] [Relationship between post-firing and each physical property] <BET specific surface area> As described above, first, for the fired powder (SiO2 / Al2O3 = 2.0) with the firing temperature in the above firing process set at 900 °C, acid treatment was carried out by changing the acid treatment conditions to obtain a powder with adjusted SiO2 / Al2O3. For each powder with adjusted SiO2 / Al2O3, further firing was carried out (post-firing process), and the BET specific surface area and total pore volume of the obtained powder were measured. The firing temperature in the post-firing process was 500, 900, 1000, and 1100 °C, and the holding time at each temperature was 1 hour. Fig. 6 shows the results of the BET specific surface area when adjusting SiO2 / Al2O3 and changing the firing temperature in the post-firing process. In addition, Fig. 7 shows the results of the total pore volume when adjusting SiO2 / Al2O3 and changing the firing temperature in the post-firing process. Note that the results of the powder dried at 110 °C are also shown simultaneously assuming that the temperature of the post-firing process is 110 °C.

[0093] As can be seen from the results of Fig. 6 and Fig. 7, it was confirmed that the BET specific surface area and the total pore volume can also be controlled by the firing temperature in the post-firing process. In addition, in the post-firing process, firing is carried out at 500 to 1000 °C, and it can be seen that a certain BET specific surface area and total pore volume are maintained even when firing is carried out at each temperature. Then, it is expected that the pore structure of the powder of the present invention is maintained even in the temperature range corresponding to the post-firing process. Comparing the powder dried at 110°C with the powder calcined at 500°C, it is found that the BET specific surface area and total pore volume are almost unchanged by calcination at 500°C. On the other hand, when post-calcination is performed at 900°C or higher, the BET specific surface area and total pore volume tend to decrease, but the higher the SiO2 / Al2O3 ratio, the smaller the decrease, and it is found that the higher the SiO2 / Al2O3 ratio, the easier it is to maintain the pore structure (higher heat resistance). Therefore, the powder of the present invention is capable of controlling the BET specific surface area and total pore volume by adjusting the calcination temperature in the calcination step, the acid treatment conditions, and the calcination temperature in the post-calcination step, and is considered to be particularly suitable for use as a catalyst, catalyst support, adsorbent, and the like. Furthermore, since the powder of the present invention maintains its pore structure even in high-temperature environments, it can withstand use in high-temperature environments and is therefore useful as a catalyst or catalyst support for reactions in high-temperature environments.

[0094] <Pore size distribution (BJH method)> Among the powders that were post-sintered, the powders that were post-sintered at 500°C and the powders that were post-sintered at 900°C were analyzed for the volume distribution of pore size by the BJH method. The results are shown in Figures 8 and 9. The results for the powders that were fired at 900°C (SiO2 / Al2O3=2.0) before the acid treatment are also shown in each figure.

[0095] From the results shown in Figures 8 and 9, it was confirmed that the obtained powder had pores with diameters of more than 8 nm and not more than 200 nm. Furthermore, from the results in Figures 8 and 9, it is inferred that there are two types of pores in the above region. Regarding this, SEM images of the powder (SiO2 / Al2O3=2.0) calcined at 900°C before the acid treatment are shown in Figures 10 and 11. Also, SEM images of the powder (SiO2 / Al2O3=13.7) calcined at 900°C after the acid treatment are shown in Figures 12 and 13. Figure 11 is an observation image at a higher magnification than that of Figure 10, and Figure 13 is an observation image at a higher magnification than that of Figure 12. The above SEM observation images were taken using Sigma 500 manufactured by Carl Zeiss Microscopy Ltd. From the SEM images in Figures 10 and 11, it can be seen that the fired powder before the acid treatment contains aluminosilicate granules formed by aggregation of metahalloysite nanotube particles. Therefore, the peaks in the 10 to 20 nm region seen in Figures 8 and 9 are considered to be pores corresponding to the tube pores of the metahalloysite nanotube particles, and the peaks in the region over 20 nm are considered to be peaks corresponding to the interparticle voids of the metahalloysite nanotube particles. Moreover, when comparing the SEM observation images in Figures 10 and 11 with those in Figures 12 and 13, it can be said that there is no change in shape due to the firing process, acid treatment process, and post-firing process. Therefore, even in the powder (SiO2 / Al2O3=13.7) that was post-firing at 900°C, the two peaks seen in Figures 8 and 9 are considered to be the peaks corresponding to the pores corresponding to the tube pores of the nanotube particles (acid-treated metahalloysite nanotube particles) and the peaks corresponding to the interparticle voids of the nanotube particles (acid-treated metahalloysite nanotube particles), respectively.

[0096] In addition, when powders with SiO2 / Al2O3 greater than 13.7 were observed with an SEM, it was found that there was no change in the shape of the nanotube particles, as shown in Figs. 12 and 13.

[0097] The amount of pores (cm) corresponding to these two peaks is 3 8 and 9, it can be seen that the pore volume per unit mass cm2 tends to increase with an increase in the SiO2 / Al2O3 molar ratio. This is thought to correspond to a decrease in the true density of the nanotube particles due to a decrease in the amount of Al2O3 (an increase in the amount of SiO2), since there is no change in the appearance of the nanotube particles before and after the acid treatment. In other words, the amount of pores per unit mass cm2 3It is considered that the pores before the acid treatment have not changed. Moreover, the rise from about 3 nm to the small pore diameter side seen in the samples after acid treatment in FIG. 8 and FIG. 9 is thought to suggest the presence of micropores.

[0098] <Micropore volume> Among the powders obtained by acid treatment and those that were post-calcined, those shown in Table 2 below were analyzed by t-plot analysis, and the micropore volume of each less than 2 nm was calculated. The Harkins-Jura-BEL.t standard curve from Microtrack-Bel was used to calculate the micropore volume. The results are shown in Table 2. Note that no micropores were observed in the 900°C calcined powder (SiO2 / Al2O3=2.0) that was not acid treated. The t-plot analysis was performed from the nitrogen adsorption isotherm. The pretreatment conditions were as follows: the acid-treated powder (110°C) was vacuum degassed at 170°C for 3.5 hours, and the other post-calcined powders (500°C, 900°C) were vacuum degassed at 300°C for 8 hours.

[0099] [Table 3]

[0100] The results shown in Table 3 confirm that the acid treatment results in a micropore volume, that is, the formation of micropores.

[0101] <Pore size distribution (GCMC method)> Among the powders that were post-sintered, the pore size area distribution was analyzed by the GCMC method for the powders that were post-sintered at 500°C and the powders that were post-sintered at 900°C. The results are shown in Figures 14 and 15. Data for the 900°C-sintered powder (SiO2 / Al2O3=2.0) that was not acid-treated is also shown in each figure. Note that the results are offset in Figures 14 and 15. The analysis by the GCMC method was carried out under the following conditions. The GCMC method, which enables consistent analysis from micropores to mesopores and macropores, performs simulations by determining parameters such as pore diameter, pore shape, adsorbed molecules, and adsorbent surface atoms. Analysis using the GCMC method was performed under the following conditions, where the simulated adsorption isotherm was close to the actual adsorption isotherm. Model (assumed pore shape): Pore ​​shape: Cylinder Surface elements: NSSO (kernel assuming the sample surface is non-uniform) PSD fitting (pore size distribution): Selected distribution function: No assumption ds (surface atomic size of adsorbent): 0.28 nm Def.pore size: Solid and Fluid Def.pore size (Pore size definition recommended by Microtrac-Bell Inc.) The pore size is defined as the midpoint of the distance at which the adsorbate overlaps the surface atoms, assuming that the actual molecular diameter is not a hard sphere.

[0102] From the results shown in Figures 14 and 15, it was confirmed that the acid treatment generates third pores having a pore size of 8 nm or less. The above analysis results correspond to the analysis results of the micropore volume. Therefore, it can be said that the powder of the present invention obtained by the acid treatment according to the above procedure also has third pores having a pore size of 8 nm or less. Also, from the results shown in Fig. 14, it can be seen that when post-baking is performed at 500°C, there are four types of pores as the third pores having a diameter of 8 nm or less: pores with a diameter of about 3 nm, pores with a diameter of about 2 nm, pores with a diameter of about 1 nm, and pores with a diameter of 1 nm or less. On the other hand, from the results shown in Fig. 15, when post-baking is performed at 900°C, pores with a diameter of about 3 nm, pores with a diameter of about 2 nm, and some pores with a diameter of about 1 nm are confirmed as the third pores having a diameter of 8 nm or less, but no pores with a diameter of 1 nm or less are observed. This indicates that the pore size distribution can be controlled by the post-calcination temperature.

[0103] <Water vapor adsorption> In the present invention, the water vapor adsorption isotherm was obtained under the following conditions and procedures, and various analyses were carried out. First, the powder was pretreated (vacuum degassing at 300°C for 8 hours), and then the adsorption / desorption isotherm with water vapor was measured using a constant volume method under the following conditions. The equilibrium waiting time is the waiting time after the adsorption equilibrium state is reached. ·Adsorption temperature: 298.15K (25℃) ·Adsorbate: Pure water ·Saturated vapor pressure: 3.169kPa (25℃) Equilibration wait time: 500 seconds (waiting time after pressure change reaches a specified value) Pretreatment device: BELPREP-vacII (Microtrack, BEL) Measurement device: BELSORP-aqua3 (Microtrack BEL) Analysis software: BELMaster Version 6.4.0.0 (Microtrack-Bell) Of the powders that were post-calcined, water vapor adsorption isotherms were obtained for the powders that were post-calcined at 500°C and for the powders that were post-calcined at 900°C. The results are shown in Figures 16 and 17. Data for the 900°C calcined powder (SiO2 / Al2O3=2.0) that was not subjected to acid treatment is also shown in each figure. The amount of water vapor adsorbed at a relative pressure of 0.9 is summarized in Table 4 below. 3 (STP) / g) is the amount of water vapor adsorbed per 1 g of powder, converted into the gas volume at 0°C and 101.325 kPa. The amount of water vapor adsorbed at a relative pressure of 0.9 shown in Table 4 was calculated by linear interpolation from two measurement points before and after the relative pressure of 0.9.

[0104] [Table 4]

[0105] 16 and 17, and the results shown in Table 4, it was confirmed that the powder of the present invention is excellent in the amount of water adsorption at a relative pressure of 0.9. Furthermore, in Fig. 16, the slope of the water adsorption amount versus relative pressure is large in the relative pressure range of about 0.3 to 0.5, and in Fig. 17, the slope is large in the relative pressure range of about 0.4 to 0.6. From this, it is considered that the material is useful as a humidity control material in each relative pressure range. In addition, it was confirmed from the results shown in Figs. 16 and 17 and Table 3 that the water adsorption characteristics change depending on the SiO2 / Al2O3 and the post-calcination temperature. In addition, since it is believed that water molecules preferentially adsorb to hydrophilic sites, it is speculated that the hydrophilic silanol groups (Si-OH) generated upon desorption of Al are influencing this.

[0106] <Toluene vapor adsorption> Of the powders that were post-calcined, toluene vapor adsorption isotherms were obtained for the powders that were post-calcined at 500°C and for the powders that were post-calcined at 900°C. The results are shown in Figures 18 and 19. Data for the 900°C calcined powder (SiO2 / Al2O3=2.0) that was not subjected to acid treatment is also shown in each figure. The toluene vapor adsorption isotherm was obtained under the following conditions and procedures, and various analyses were carried out. First, the powder was pretreated (vacuum degassing at 300°C for 8 hours), and then the adsorption / desorption isotherm with toluene vapor was measured using a constant volume method under the following conditions. The equilibrium waiting time is the waiting time after the adsorption equilibrium state is reached. ·Adsorption temperature: 298.15K (25℃) Adsorbate: Toluene ·Saturated vapor pressure: 3.822kPa (25℃) Equilibration wait time: Pressure change within 0.2% of pressure gauge reading over 500 seconds Pretreatment device: BELPREP-vacII (Microtrack, BEL) Measurement device: BELSORP-MaxII (Microtrack BEL) Analysis software: BELMaster Version 6.4.0.0 (Microtrack-Bell) The amount of toluene vapor adsorbed at a relative pressure of 0.9 is summarized in Table 5 below. 3 (STP) / g) is the amount of toluene adsorbed per gram of powder, converted into the gas volume at 0°C and 101.325 kPa.

[0107] [Table 5]

[0108] 18 and 19, and the results shown in Table 5, it was confirmed that the powder of the present invention is excellent in the amount of toluene vapor adsorbed at a relative pressure of 0.9. 18 and 19, the slope of the adsorption amount versus relative pressure is large in the region where the relative pressure is about 0.1 (region where adsorption in micropores is likely to occur), and it can be said that the powder of the present invention has the property of easily capturing low concentrations of toluene. Therefore, it can be said that the powder of the present invention is useful as a catalyst, catalyst carrier, adsorbent, etc. involved in the reaction of organic matter. In addition, it was confirmed from the results shown in Figs. 18 and 19 and Table 5 that the toluene adsorption characteristics change depending on the SiO2 / Al2O3 and the post-calcination temperature. In addition, since toluene molecules are thought to preferentially adsorb to lipophilic sites, it is speculated that lipophilic siloxane bonds (Si-O-Si) that are thought to have been formed due to the desorption of Al and post-calcination are having an effect.

[0109] In addition, solid-state nuclear magnetic resonance measurements ( 29 Si (CPMAS method) was performed, and Q 2 =Si(OSi)2OH2, Q 3 =Si(OSi)3OH, and Q 4On the other hand, the peak corresponding to =Si(OSi)4 was hardly observed in the powders that were post-calcined at 500°C after acid treatment (SiO2 / Al2O3 = 13.7 and 189.0). 2 , Q 3 and Q 4 A peak corresponding to was confirmed. The above results suggest that in the powders that were post-calcined at 500°C after acid treatment (SiO2 / Al2O3 = 13.7 and 189.0), silanol groups and siloxane bonds were formed by the acid treatment and calcination.

[0110] From the results of the water adsorption amount, the toluene adsorption amount, and the solid-state nuclear magnetic resonance measurement, it can be said that the powder of the present invention has hydrophilic adsorption sites and hydrophobic adsorption sites, and has the ability to capture various molecules. In addition, since the powder of the present invention can be said to have a unique microscopic space, it is considered that the powder of the present invention is also useful as a sustained release material.

[0111] <Properties of solid acids> Among the powders that were post-calcined, the powders that were post-calcined at 500°C and the powders that were post-calcined at 900°C were evaluated for their solid acid properties. For comparison, the powders that were calcined at 900°C (SiO2 / Al2O3=2.0) before the acid treatment were also evaluated in the same manner. The results are shown in Table 6 below and in Figures 20 and 21. The evaluation was performed by ammonia temperature programmed desorption method (hereinafter also referred to as "NH3-TPD") under the following conditions. Equipment used: Fully automatic thermal desorption spectrometer (TPD-1-ATw, manufactured by Microtrack Bell) Sample size: Approx. 50 mg Measurement range: 100~800℃ Detector: Quadrupole mass spectrometer Detected fragment: m / z 16 The measurement program for NH3-TPD is as follows: Pretreatment: The temperature is raised from room temperature to 500°C at 10°C / min, and then held at 500°C for 1 hour. Then, the temperature is naturally lowered to 100°C in about 1.5 hours. During this time, He gas is circulated at 50mL / min. NH3 adsorption: After reaching 100°C, maintain the temperature at 100°C for 30 minutes. During this time, He gas containing 0.5% by volume of NH3 gas is passed through at 100 mL / min. Desorption of excess NH3: Hold at 100°C and pass He gas through at 50 mL / min for 30 minutes. Temperature programmed desorption measurement: The temperature is raised from 100°C to 800°C at 10°C / min. During this time, He gas is passed through at 50mL / min.

[0112] FIG. 20 shows the results of NH3-TPD measurement of powders post-calcined at 500°C, and FIG. 21 shows the results of NH3-TPD measurement of powders post-calcined at 900°C. A solid acid is a solid that has spots called acid sites that show acidity on its surface. Here, NH3 molecules adsorbed on acid sites with weak acid strength tend to desorb at low temperatures, while NH3 molecules adsorbed on acid sites with strong acid strength tend to desorb at high temperatures. The amount of NH3 molecules desorbed by heating corresponds to the amount of acid sites in the solid acid. From the results shown in FIG. 20 and FIG. 21, it is apparent that there are peaks near 200° C. and near 500° C., suggesting the presence of weak and strong acid sites. Table 6 is an analysis of the amount of NH3 molecules desorbed from the measurement results shown in Figures 20 and 21, and shows the total amount desorbed, the amount desorbed at 200°C or higher, the amount desorbed at 300°C or higher, and the amount desorbed at 400°C or higher, respectively.

[0113] [Table 6]

[0114] The results shown in Table 6 suggest that the powder of the present invention has a larger amount of desorption at high temperatures (e.g., 400°C or higher) than the calcined powder before the acid treatment, suggesting that acid sites with strong acid strength appear. Also, since the total amount of desorption is larger than that of the calcined powder before the acid treatment, it can be said that the powder of the present invention tends to have a larger amount of acid (amount of acid sites). On the other hand, it was confirmed that the solid acidity and acid strength can be adjusted by SiO2 / Al2O3 and the post-calcination temperature. The powder of the present invention is also useful as a solid acid catalyst because it has a strong acid site where NH3 molecules do not leave even at 400° C. In addition, the powder of the present invention can adjust the solid acid amount and acid strength (solid acid properties) according to the desired reaction.

[0115] <Catalyst properties> The catalytic properties were evaluated using powders with different SiO2 / Al2O3 ratios obtained by acid treatment and washing under various conditions, powders obtained by post-calcination at 500°C for the dried powders, and powders obtained by post-calcination at 900°C for the dried powders. For comparison, the catalytic properties were evaluated using the calcined powder before the acid treatment (calcined at 900°C) and a commercially available zeolite powder. Although the powder calcined at 900°C before the acid treatment was not post-calcined, the results are shown in the 110°C column in Table 7 for convenience. The catalytic properties were evaluated by proceeding with a solid acid catalytic reaction according to the following procedure and evaluating the yield. First, a reaction solution was prepared by adding 0.5 mmol of glycerol tributyrate to 2.5 mL of methanol, and the solution was placed in a pressure-resistant glass reactor. To the reaction solution, 0.1 g of the catalyst sample was added, and the mixture was heated to 180° C. and stirred for 4 hours to cause the following transesterification reaction to proceed, thereby obtaining the target compound ((t) in the following formula).

[0116] [ka]

[0117] After stirring, the target compound was quantitatively determined by gas chromatography to determine the yield. The analytical conditions were as follows. The results are shown in Table 7. Analytical equipment: GC-2010 (Shimadzu Corporation) Column: Restek Rtx-5MS capillary column Column length: 30m ·Inner diameter: 0.25mm Film thickness: 0.25μm

[0118] [Table 7]

[0119] From the results shown in Table 7, it was confirmed that the powder of the present invention has superior catalytic properties compared to that before the acid treatment. It was also confirmed that the powder of the present invention has high catalytic properties even against commercially available zeolites. The reason why the powder of the present invention exhibits excellent catalytic properties is believed to be that not only the properties of the solid acid but also the properties of the pore structure and surface properties are simultaneously involved. When the powder of the present invention is used as a catalyst for reactions other than those described above, the optimum physical properties may differ. As described above, the powder of the present invention can control various characteristics and physical properties, so that the physical properties can be adjusted according to the application. The physical properties of the powder of the present invention can be controlled by SiO2 / Al2O3 and the post-calcination temperature, etc., as described above.

[0120] <Methylene blue adsorption> The amount of methylene blue adsorbed was measured by the method described above for the powder that had been subjected to the acid treatment, washing, and drying at 110° C., the powder that had been post-calcined at 500° C., and the powder that had been post-calcined at 900° C. The results are shown in Table 8 below. For comparison, the same measurement was also carried out on powder fired at 900°C (SiO2 / Al2O3 = 2.0) before the acid treatment, and the amount of methylene blue adsorbed was found to be 36.5 mg / g.

[0121] [Table 8]

[0122] From the results shown in Table 8, it was confirmed that the powder of the present invention has a large adsorption amount of methylene blue and is useful as an adsorbent (e.g., a cation adsorbent), etc. In addition, since the powder of the present invention can adsorb a dye, it can be said to be useful as a dye or coloring material.

[0123] The powder of the present invention is a powder (novel spatial material) having a novel porous structure that simultaneously has pores (e.g., 10 to 20 nm) derived from nanotubes and micropores (e.g., four types of pores, e.g., about 3 nm, about 2 nm, about 1 nm, and 1 nm or less) other than the pores derived from nanotubes. The powder of the present invention is not limited to the applications specifically measured in the examples, and can be used in various applications, such as those mentioned above.

Claims

1. A 2 O 3 SiO content 2 A powder containing aluminosilicate particles having a molar ratio of the content of: the aluminosilicate particles include nanotube particles; The aluminosilicate particles have pores with diameters of more than 8 nm and not more than 200 nm.

2. The powder according to claim 1 , wherein the aluminosilicate particles have, as the pores, first pores derived from the nanotube particles and second pores different from the first pores.

3. The powder according to claim 1 , wherein the aluminosilicate particles have pores with a pore size of 8 nm or less.

4. The powder according to claim 1 , wherein the aluminosilicate particles have pores with a pore size of 8 nm or less and pores with a pore size of more than 8 nm and less than 200 nm.

5. 2. The powder according to claim 1, wherein the aluminosilicate particles have first pores derived from the nanotubular particles and having a pore diameter of more than 8 nm and not more than 200 nm, second pores different from the first pores and having a pore diameter of more than 8 nm and not more than 200 nm, and pores having a pore diameter of 8 nm or less.

6. BET specific surface area: 50 m 2 The powder according to any one of claims 1 to 5, wherein the molecular weight of the powder is 1 / g or more.

7. Total pore volume is 0.40 cm 3 The powder according to any one of claims 1 to 5, wherein the molecular weight of the powder is 1 / g or more.

8. The volume of the micropore is 0.01 cm 3 The powder according to any one of claims 1 to 5, wherein the molecular weight of the powder is 1 / g or more.

9. The amount of water vapor adsorbed is 120 cm at a relative pressure of 0.

9. 3 The powder according to any one of claims 1 to 5, wherein the molecular weight of the powder is 1 / g or more.

10. The amount of toluene vapor adsorbed is 40 cm at a relative pressure of 0.

9. 3 The powder according to any one of claims 1 to 5, wherein the molecular weight of the powder is 1 / g or more.

11. NH at 400°C or higher measured by thermal desorption spectroscopy 3 The powder according to any one of claims 1 to 5, wherein the amount of desorption is 4.0 µmol / g or more.

12. The powder according to any one of claims 1 to 5, having an adsorption amount of methylene blue of 40 mg / g or more.

13. The powder according to any one of claims 1 to 5, having an average particle size of 0.5 to 200 µm.

14. A powder containing aluminosilicate particles is calcined at 600 to 900° C. to obtain a calcined powder; A method for producing a powder, comprising subjecting the calcined powder to an acid treatment, the aluminosilicate particles include nanotube particles; The aluminosilicate particles are Al 2 O 3 SiO content 2 The molar ratio of the content of is less than 2.1.

Citation Information

Patent Citations

  • Method for preparing magnetic halloysite molecularly imprinted polymer with specific adsorption to 2,4-dichlorophenoxyacetic acid

    CN103613722A

  • Nickel-based catalyst, preparation method and application thereof

    CN113522295A

  • Antibacterial temperature-regulating difunctional fiber and preparation method thereof

    CN117230540A

  • Magnetic viscous fluid

    JP2006286890A

  • Method of producing NANO silicon

    JP2023044813A